The Effect of Company Size and Earnings Management On Corporate Social Responsibility (CSR) In Manufacturing Companies Listed On The Indonesia Stock Exchange For The 2017-2019 Period - Dedy Ibrahim Rauf; A Fadel Muhammad; Dian Faradilla J.A; Nur Fitri; Amelia Kartika; A Saddiyah Sebrina G (STIE Amkop Makassar, 2023)
The Influence of Company Size and Profit Management on Corporate Social Responsibility (CSR) in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2017-2019 Period (supervised by Hisnol Jamali and Muzdalifah). This research aims to determine the influence of company size and earnings management on corporate social responsibility (CSR) in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This data collection uses secondary data obtained from financial reports using purposive sampling techniques. The population is all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2017-2019 period, a total of 54 companies. Meanwhile, the samples taken were 30 companies. The results of the research variable data have been tested for classical assumptions in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. The data analysis method uses multiple linear regression techniques. The research results simultaneously show that company size and earnings management do not have a significant effect on corporate social responsibility. The partial research results show that company size has a negative and insignificant effect on corporate social responsibility, and earnings management has a negative and insignificant effect on corporate social responsibility.